Kajian Psikolinguistik Terkait Dampak Interkasi Sosial Dan Paparan Media Digital Terhadap Pemerolehan Bahasa Anak Usia Dini (4 Tahun) - Nikmatul Wahidah (PT. Willy Print Art, 2025)
This study aims to describe the influence of social interaction and the impact of digital media exposure on the language acquisition of four-year-old children from a psycholinguistic perspective. Using a qualitative descriptive approach, the study involved four four-year-old children with varying patterns of social interaction and device use. Data were collected through observation, interviews, and documentation of the children's conversations. The results indicate that children's language acquisition is strongly influenced by the quality of two-way social interaction and the type of linguistic input received. Children who receive consistent communication demonstrate more mature language development (phonology, syntax, and pragmatics). Conversely, children who are exposed to digital media more frequently and without supervision tend to experience speech delay, characterized by limited vocabulary and unclear articulation. This study concludes that positive social interaction and supervision of digital media use are key factors in determining early childhood language development.